Overview of BLOOFINZ/INDITUN investigations of the southern bluefin spawning region off northwest Australia, January–March 2022 - Michael R. Landry; Raúl Laiz-Carrión; Sven A. Kranz; Karen E. Selph; Michael R. Stukel; Estrella Malca; David Die; Lynnath E. Beckley; Moira Décima; Rasmus Swalethorp; José M. Quintanilla; Natalia Yingling; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

Spatiotemporal Variability of Dendroecological Indicators in Pedunculate Oak ( Quercus robur L.) Tree‐Rings Across Europe in Relation to Species Distribution Models - Andrei Popa; Jernej Jevšenak; Marcin Dyderski; Radosław Puchałka; Allan Buras; Ionel Popa; Martin Wilmking; Aleksandra Kalisty; Catalin‐Constantin Roibu; Marcin Jakubowski; Eric Thurm; Martin Šenfeldr; et al. (Global Change Biology, 2025)
Climate is a primary, but non‐stationary, driver of tree growth. Climate change is altering the sensitivity of forest growth to water availability and temperature over time. It is considered that pedunculate oak ( Quercus robur L.) will cope with the changing climatic conditions in Europe in the near future. However, while species distribution models project expansion zones, they also identify reductions in occurrence at the dry and warm distribution margins. Whereas species distribution models primarily rely on occurrence data, tree rings—given their long‐term perspective and their use in empirical models—can provide a mechanistic view of forest growth dynamics, including temporally changing climate responses. Increased climate sensitivity and growth synchrony are key dendroecological indicators of tree stress. Here, we used an unprecedented network of 150 Q. robur sites (over 3300 trees), covering the full projected range of contracting to persistent areas across Europe, to assess the dendroecological indicators over recent decades in relation to species distribution model predictions. We reveal that oaks in areas projected to experience range contraction exhibited greater sensitivity to current growing season climatic conditions, whereas those in persistence areas responded more strongly to previous season conditions. Growth synchrony among trees was higher in the contraction areas, but showed no significant increasing trend over the last 70 years, as expected from ecotone theory. Temporal shifts in climate sensitivity were stronger for temperature and vapor pressure deficit in the persistence areas, whereas the climatic water balance gained importance in the contraction zones. These findings suggest that Q. robur growth is not yet being severely affected by climate change, and that the species is currently coping well with the climate changes, even in regions with projected range contractions, thereby challenging statistically derived scenarios of range shift based on species distribution models.

Climate at play: Norway spruce responses to weather and climate conditions across latitudinal and elevational gradients of Eastern Europe - Andrei Popa; Ionel Popa; Āris Jansons; Oskars Krišāns; Pauls Zeltiņs; Roberts Matisons (Agricultural and Forest Meteorology, 2025)

Temperature-driven shifts in spatiotemporal stability of climate-growth responses of Douglas-fir (Pseudotsuga menziesii) from the southern Baltic Sea region - Marcin Klisz; Radosław Puchałka; Mariusz Gławenda; Marcin Koprowski; Roberts Matisons; Sandra Metslaid; Aleksei Potapov; Tobias Scharnweber; Eric Andreas Thurm; Rita Verbylaite; Adomas Vitas; Martin Wilmking; et al. (Agricultural and Forest Meteorology, 2025)

Radial growth models for Pedunculate Oak in the Baltics, Latvia - Agnese Anta Liepiņa; Roberts Matisons; Kārlis Bičkovskis; Guntis Brūmelis; Āris Jansons (Ecological Modelling, 2025)

Should I stay or should I go? Meteorological effects on radial growth in introduced lodgepole pine provenances - Diāna Jansone; Roberts Matisons; Didzis Elferts; Kalev Jõgiste; Baiba Jansone; Inga Straupe; Āris Jansons (Dendrochronologia, 2025)

A new hope: Condition of young stands suggests natural recovery of European ash in Northern Europe - Ilze Matisone; Darta Klavina; Roberts Matisons; Keitlina Krastina; Annija Aunina; Baiba Krivmane; Maryna Ramanenka; Kateryna Davydenko (Forest Ecology and Management, 2025)

Geographic variation in resistance of Scots pine (Pinus sylvestris L.) to wind loading across different wind environments in Europe - Andris Seipulis; Barry Gardiner; Heli Peltola; Bruce Nicoll; Steffen Rust; Roberts Matisons; Didzis Elferts; Oskars Krišāns; Aris Jansons (Forest Ecology and Management, 2024)

Response of underplanted European beech to shelterwood thinning at the northeasternmost forpost plantation in Europe - Ilze Matisone; Ieva Jaunslaviete; Andis Adamovičs; Roberts Matisons; Āris Jansons (New Forests, 2024)

Productivity of local Norway spruce clones relates to weather sensitivity of height increment in the eastern Baltic region - Roberts Matisons; Pauls Zeltiņš; Rolands Kāpostiņš; Kristaps Ozoliņš; Āris Jansons (Dendrochronologia, 2024)

Meteorological conditions have a complex effect on the tree-ring width of horse chestnut Aesculus hippocastanum in a forest plantation in Latvia - Diāna Jansone; Roberts Matisons; Āris Jansons; Ieva Jaunslaviete (Dendrochronologia, 2023)

Black locust ( Robinia pseudoacacia L.) range contraction and expansion in Europe under changing climate - Radosław Puchałka; Marcin K. Dyderski; Michaela Vítková; Jiří Sádlo; Marcin Klisz; Maksym Netsvetov; Yulia Prokopuk; Roberts Matisons; Marcin Mionskowski; Tomasz Wojda; Marcin Koprowski; Andrzej M. Jagodziński (Global Change Biology, 2021)
Robinia pseudoacacia is one of the most frequent non‐native species in Europe. It is a fast‐growing tree of high economic and cultural importance. On the other hand, it is an invasive species, causing changes in soil chemistry and light regime, and consequently altering the plant communities. Previously published models developed for the potential distribution of R. pseudoacacia concerned 2070, and were based mainly on data from Western and Central Europe; here we extended these findings and included additional data from Eastern Europe. To fill the gap in current knowledge of R. pseudoacacia distribution and improve the reliability of forecasts, we aimed to (i) determine the extent to which the outcome of range modeling will be affected by complementing R. pseudoacacia occurrence data with sites from Central, Southeastern, and Eastern Europe, (ii) identify and quantify the changes in the availability of climate niches for 2050 and 2070, and discuss their impacts on forest management and nature conservation. We showed that the majority of the range changes expected in 2070 will occur as early as 2050. In comparison to previous studies, we demonstrated a greater eastward shift of potential niches of this species and a greater decline of potential niches in Southern Europe. Consequently, future climatic conditions will likely favor the occurrence of R. pseudoacacia in Central and Northeastern Europe where this species is still absent or relatively rare. There, controlling the spread of R. pseudoacacia will require monitoring sources of invasion in the landscape and reducing the occurrence of this species. The expected effects of climate change will likely be observed 20 years earlier than previously forecasted. Hence we highlighted the urgent need for acceleration of policies aimed at climate change mitigation in Europe. Also, our results showed the need for using more complete distribution data to analyze potential niche models.

Tree growth influenced by warming winter climate and summer moisture availability in northern temperate forests - Jill E. Harvey; Marko Smiljanić; Tobias Scharnweber; Allan Buras; Anna Cedro; Roberto Cruz‐García; Igor Drobyshev; Karolina Janecka; Āris Jansons; Ryszard Kaczka; Marcin Klisz; Alar Läänelaid; et al. (Global Change Biology, 2020)
The role of future forests in global biogeochemical cycles will depend on how different tree species respond to climate. Interpreting the response of forest growth to climate change requires an understanding of the temporal and spatial patterns of seasonal climatic influences on the growth of common tree species. We constructed a new network of 310 tree‐ring width chronologies from three common tree species ( Quercus robur , Pinus sylvestris and Fagus sylvatica ) collected for different ecological, management and climate purposes in the south Baltic Sea region at the border of three bioclimatic zones (temperate continental, oceanic, southern boreal). The major climate factors (temperature, precipitation, drought) affecting tree growth at monthly and seasonal scales were identified. Our analysis documents that 20th century Scots pine and deciduous species growth is generally controlled by different climate parameters, and that summer moisture availability is increasingly important for the growth of deciduous species examined. We report changes in the influence of winter climate variables over the last decades, where a decreasing influence of late winter temperature on deciduous tree growth and an increasing influence of winter temperature on Scots pine growth was found. By comparing climate–growth responses for the 1943–1972 and 1973–2002 periods and characterizing site‐level growth response stability, a descriptive application of spatial segregation analysis distinguished sites with stable responses to dominant climate parameters (northeast of the study region), and sites that collectively showed unstable responses to winter climate (southeast of the study region). The findings presented here highlight the temporally unstable and nonuniform responses of tree growth to climate variability, and that there are geographical coherent regions where these changes are similar. Considering continued climate change in the future, our results provide important regional perspectives on recent broad‐scale climate–growth relationships for trees across the temperate to boreal forest transition around the south Baltic Sea.

Influence of climate on tree-ring and earlywood vessel formation in Quercus robur in Latvia - Roberts Matisons; Guntis Brūmelis (Trees, 2012)